Class I myosin Myo1e regulates TLR4-triggered macrophage spreading, chemokine release, and antigen presentation via MHC class II - Wenzel, Jens; Ouderkirk, Jessica L.; Krendel, Mira; Lang, Roland (European Journal of Immunology, 2015)
TLR-mediated recognition of microbial danger induces substantial changes in macrophage migration, adherence, and phagocytosis. Recently, we described the LPS-regulated phosphorylation of many cytoskeleton-associated proteins by phosphoproteomics. The functional role of these cytoskeletal and motor proteins in innate immune cell responses is largely unexplored. Here, we first identified both long-tailed class I myosins Myo1e and Myo1f as important contributors to LPS-triggered macrophage spreading. Mouse bone marrow-derived macrophages and DCs deficient in Myo1e selectively secreted increased amounts of the chemokine CCL2. In addition, the cell surface expression of MHC class II (MHC-II) on both cell types was reduced in the absence of Myo1e. However, transcriptional changes in CCL2 and MHC-II were not observed in the absence of Myo1e, indicating that Myo1e regulates specific intracellular transport processes. The capacity of macrophages and DCs lacking Myo1e to stimulate antigen-specific CD4(+) T-cell proliferation was impaired, consistent with the reduced MHC-II surface protein levels. Surprisingly, in Myo1e-deficient DCs, the proteolytic cleavage of endocytosed antigen was also increased. Together, our results provide evidence for a non-redundant function of the motor protein Myo1e in the regulation of TLR4-controlled, cytoskeleton-associated functional properties of macrophages and DCs, and in induction of a full MHC-II-restricted adaptive immune response.
EVALuna2:7660